Risk factors and drugs that trigger the onset of Stevens-Johnson syndrome and toxic epidermal necrolysis: A population-based cohort study using the Shizuoka Kokuho databaseCapsule Summary - Nanako Ubukata, MS; Eiji Nakatani, PhD; Hideo Hashizume, MD, PhD; Hatoko Sasaki, Dr PH; Yoshiki Miyachi, MD, PhD (Elsevier, 2023)
Background: Evidence of factors associated with Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) from population-based studies is scarce. Objective: We aimed to identify the incidence, risk factors, and drugs that trigger the development of SJS/TEN in the general population. Methods: A regional, population-based, longitudinal cohort with 2,398,393 Japanese individuals was analyzed using the Shizuoka Kokuho Database from 2012 to 2020. Results: Among 1,909,570 individuals, 223 (0.01%, 2.3 cases/100,000 person-years) patients were diagnosed with SJS/TEN during the observational period of a maximum of 7.5 years. In a multivariable analysis, the risks of SJS/TEN were an older age, and the presence of type 2 diabetes, peripheral vascular disease, and systemic autoimmune diseases. The administration of drugs, such as immune checkpoint inhibitors, insulin, and type 2 diabetes agents, triggered the onset of SJS/TEN. Limitations: The results may apply only to the Japanese population. Conclusion: In this cohort population from a database representing the general population, the risks of developing SJS/TEN were old age and a history of type 2 diabetes, peripheral vascular disease, and systemic autoimmune disease. Furthermore, in addition to previously reported drugs, the administration of immune checkpoint inhibitors, insulin, and type 2 diabetes agents, may trigger the development of SJS/TEN.